Penyegaran Pendidikan Islam ; Wacana Redevinisi Dan Dekonstruksi - Fatahillah, Faizal Rois (J-PAI: Jurnal Pendidikan Agama Islam, 2014)
The Development of Islamic Education requires strong and detail epistemology that can only be resulted from complete understanding about classical inheritance about Islamic Education and then combined with detail understanding about issue and challenge that faced by Islamic Education at present and future. In this context, a scholar of Islamiceducation requires to know classical inheritance about Islamic Education in his major well, and then mapping and searching the relevance to the condition of Islamic Education at the present and future.keywords: Islamic Education, Redivinisi, Deconstruction.